Digital Poetry And Cultural Identity: Structural Study of The Poems “Hanyalah Anak Desa” and “Sungguh Terlalu, Sangat Menderita” by Gimin Saputra - Aris Yulantomo; Rian Hidayat; Yulia Nelfita (Jurnal IKADBUDI, 2025)
This study analyzes the meaning and structure of the poems "Hanyalah Anak Desa" and "Sungguh Terlalu, Sangat Menderita" by Gimin Saputra. Using a structuralist approach, the research explores physical elements (diction, rhyme, rhythm, typography) and inner elements (theme, tone, atmosphere, moral message) to understand how the poems reflect social and cultural realities. "Hanyalah Anak Desa" highlights the struggle of a rural child overcoming economic limitations to achieve education, while "Sungguh Terlalu, Sangat Menderita" voices criticism of social injustice. The analysis reveals that physical and inner elements harmoniously support each other in creating profound meanings, emphasizing individual struggles within the context of social inequality. These findings are highly relevant to the Indonesian social context, where poetry serves as a medium for reflection and social critique. This study underscores the importance of structural and semantic analysis in unraveling the complexities of poetry as a rich cultural expression. Keywords: poetry; structural analysis; social critique; Gimin Saputra; Indonesian literature